ESTUDIOS SOBRE LA MEDULA OSEA I LOS TRES MIELOGRAMAS - GONZALEZ GUZMAN, IGNACIO (Instituto Higiene, CD MEXICO, DF, MEX, 1949)
In memory of Dr Pio del Rio-Hortega the 18 conclusions resulting from his study of the microglia of the central nervous system by his silver staining technique are presented
BOL INST ESTUD MED BIOL
Keywords: ESTUDIOS, MEDULA -OSEA, MIELOGRAMAS; CIENCIAS MEDICAS; OTRAS ESPECIALIDADES MEDICAS (ESPECIFICAR); MEDICINA BIOQUIMICA